(3SDGdGJ aj GdMceIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3jHjf eG eYfi GdJfbd HGdbhI aEf HGdTF GdPi jOQc efG GdeYbhdGJ bO HGf Gfg eLQO Yf GdeGOI s
(3BNQgG (B:s
(3Ydi EHQGO Led gPg GdYdhe GdePchQg Hd Ydi TQM JaGUdgG hGdWQjb EdjgG ddQGZHjf ai eYhbgG dGFM hGddg Gdehab ddNjQGJ JeJ hGdMeO ddg Mb MeOg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3djOf s
Keywords: (3GdadSaI hGdefWbs